Damage identification in RC bridges by confronting two approaches: visual inspection and numerical analysis - Ayad Mohammed; Boumechra Nadir; Hamdaoui Karim (Fracture and Structural Integrity)
The present article aims to summarize the research study that was conducted the efficiency of methods and techniques designed for the detection and localization of faults in civil engineering structures, particularly in bridge structures. The diagnosis of a real reinforced concrete bridge by a visual inspection is presented. Then, three numerical damage detection and localization methods, namely the eigenfrequency change method, the eigenstrain change method (Coordinate Modal Assurance Criterion CO-MAC), and the strain energy change method, are explicitly presented. Furthermore, the modeling of the bridge, before and after damage, using the Ansys software was carried out in order to identify all possible bridge defects. Afterward, the numerical results are graphically represented using the above mentioned methods. This made it possible to confirm the initial diagnosis and hence assess the damages observed on site and also in other zones.